2019
DOI: 10.1007/s13205-019-1572-4
|View full text |Cite
|
Sign up to set email alerts
|

Insights into multifaceted activities of CysK for therapeutic interventions

Abstract: CysK (O-acetylserine sulfhydrylase) is a pyridoxal-5′ phosphate-dependent enzyme which catalyzes the second step of the de novo cysteine biosynthesis pathway by converting O-acetyl serine (OAS) into l-cysteine in the presence of sulfide. The first step of the cysteine biosynthesis involves formation of OAS from serine and acetyl CoA by CysE (serine acetyltransferase). Apart from role of CysK in cysteine biosynthesis, recent studies have revealed various additional roles of this enzyme in bacterial physiology. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 104 publications
0
10
0
Order By: Relevance
“…In Staphylococcus mutans, O-acetylserine sulfatase (CysK) overexpression increases cysteine synthesis, which in turn promotes biofilm formation (31). Furthermore, in vitro testing has showed that CysK gene deletion inhibits biofilm formation by reducing polysaccharide production (32). Thus, we also explored whether a similar phenomenon occurs in S. suis.…”
Section: Discussionmentioning
confidence: 98%
“…In Staphylococcus mutans, O-acetylserine sulfatase (CysK) overexpression increases cysteine synthesis, which in turn promotes biofilm formation (31). Furthermore, in vitro testing has showed that CysK gene deletion inhibits biofilm formation by reducing polysaccharide production (32). Thus, we also explored whether a similar phenomenon occurs in S. suis.…”
Section: Discussionmentioning
confidence: 98%
“…For L. reuteri LR1, the possible moonlighting function can be proposed for Cysteine synthase A (CysK) whose secretion can be associated with the presence of K. pneumoniae (ReKl and ReRhKl). CysK typically carries out the second step in the pathway of cysteine biosynthesis, synthesizing cysteine from sulfide (H 2 S) and O-acetyl-L-serine; however, it has been shown that in certain bacteria, including Lactobacillus casei, this enzyme can perform cysteine desulfurization leading to the formation of pyruvate, ammonia (NH 3 ) and H 2 S [47]. Recent investigations demonstrate that the presence of both NH 3 and H 2 S during cultivation significantly influenced bacterial physiology [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…However, selective targeting remains a major challenge to drug discovery groups due to the paucity of information about details of complex formation and dissociation. Enzymes of cysteine biosynthesis pathway, including CS (CysK), have been considered as potential drug targets ( 36 , 37 , 38 , 39 , 40 ). Using structure-based in silico screening, multiple studies have identified several inhibitors against CS and its homologue, CysM ( 41 ).…”
Section: Discussionmentioning
confidence: 99%